(untitled) - Bradford, Shannon (New York, 2002)
Learn the secrets to surviving–and thriving–in today’s uncertain economy with the brain-boosting techniques found in Brain Power. Brain Power shows you how to succeed in business by augmenting your patterns of thinking and creativity and becoming a more effective communicator. Through real-world examples, self-quizzes, and checklists, you’ll discover how to redirect your brain in order to move ahead in your career, avoid frustrating miscommunication, influence others, and increase your productivity. In this groundbreaking new book, consultant Shannon Bradford teaches you how to develop the thinking skills most critical to succeeding in the current economy: 1) Changing the way you see business; 2) Generating ideas; 3) Getting things done; and 4) Building good working relationships. Bradford presents an interdisciplinary approach to cognitive skills and the brain, explaining how to maximize thinking and communication, solve problems, and respond to stressful situations by pairing her seven Brain Operating Principles with tools for action
Keywords: Business communication